"THIS HERE'S A HUMAN MENU." VALUE COCREATION ON TINDER - Cavalcanti, Hellen Taynan; Abreu, Nelsio Rodrigues (Animus. Revista Interamericana de Comunicação Midiática, 2021)
The purpose of this paper is to analyse value cocreation of exchanges on the Tinder app. Netnography was conducted, including participant observation and 13 in-depth interviews. The results were analysed using Bardin's content analysis. The exchanges exaggerate the value proposition of the service, and the online environment makes coordination difficult. Value cocreation more closely resembles the creation of value by the user rather than by the app, considering the fragility of the institutional aspects. Tinder allows relationships between consumers that are similar to marketing relationships, with opportunities for choice, accumulation, exchange, and disposal that constitute objectification. Keywords: Value cocreation. Tinder. Netnography.